PENGARUH MODEL MODIFIED FREE INQUIRY TERHADAP PEMAHAMAN SISWA MATERI AKU DAN KEBUTUHANKU KELAS IV SDN 11 RIAU SILIP - Desy Sapitry Yulandari; Erika Fitri Wardani; Diana Pramesti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was prompted by students’ suboptimal comprehension of the “Me and My Needs” curriculum. The study was carried out to investigate a model modified to influence students’ understanding of the “Me and My Needs” curriculum among fourth-grade students at SDN 11 Riau Silip. This study employed an experimental method using a pre-test and post-test group with a pre-experimental design. Population and sample of the study comprised all 30 fourth-grade students at SDN 11 Riau Silip, a total sampling technique was employed to select the participants, while data were collected through a essay test consisting of 10 items. The results were analyzed using the Shapiro-Wilk normality test, with the paired-sample t-test used to test the assumptions. The results of the normality test indicated that the pretest data followed a normal distribution (Sig. 0.185 > 0.05), as did the posttest data (Sig. 0.279 > 0.05). The findings of the paired-sample t-test indicate that the significance value was level of 0.000 (<0.05) was obtained. The statistical findings support Hypothesis (Ha) is accepted and hypothesis (H0) is rejected. therefore, the research findings show the implementation of the modified free inquiry model contributes to the understanding of fourth-grade students at SDN 11 Riau Silip regarding the Me and My Needs material.